Do luto à luta: notícias do serviço social sobre uma guerra particular - Caritá, Karina Pierrobon (2010)
This dissertation aims to deepen the knowledge about indirect victims of homicide, their thoughts towards the violent fact and their ways of resistance and fight against violence. It also intends to evaluate and demonstrate the possibilities professionals have to mobilize transformative powers of these individuals and situation from the experience of care at the Center of Reference and Support to Victims CRAVI. This is the Citizenship Group, held in an interdisciplinary way, by professionals of Psychology and Social Work. This research began revealing the approaches to the professional world of murder victims‟ relatives directly through Internship, End of Course Work and Research. In a second step, we propose a discussion of violence and victimization based on the use of historical and dialectical materialism. Regarding the challenges encountered in working with indirect victims, a multidisciplinary group experience is problematized and then, the methodology of the Citizenship Group is presented and the interdisciplinarity as an ethical-political position towards autonomy, deepening democracy and citizenship exercise is discussed. We present the research methodology and the work with the 2006 and 2009 Citizenship Groups, emphasizing, through speeches of indirect victims, this experience‟s development and productions. After this path, we suggest some guidance for Social Workers‟ professional practice in working with victims of violence relatives, aiming the mobilization of the transformation powers in these subjects, from the experience with Citizenship Groups